PRESERVING THE SOUNDSCAPE OF FOREST IN THE URBAN AREA THROUGH ART SONG - Alia Farahin Abd Wahab; Khairunnisa Diyana Md Noor (Journal of Islamic, Social, Economics and Development, 2024)
In the past few years, it was found that the forest area and the nature area in Malaysia are diminishing. The forest area that is situated in the urban area is mainly affected by this. The main reason for the diminishing size of the forest area was urbanization and the development of the country. Due to this fact, I decided to preserve the soundscape of the forest in the urban area through music. In order to do this, recordings of the soundscape were done in the forest. The soundscape was analysed and transcribed and made into a new song composition. The process of preserving the soundscape is done to document the soundscape of the forest through music and songs. The paper talks about the process of documenting the soundscape, the analysis process, and the composition process of the art song and the meaning behind the music.